KEWENANGAN APARAT PENGAWASAN INTERN PEMERINTAH DALAM MENENTUKAN KERUGIAN KEUANGAN NEGARA - Dharma, Widya Castrena Budi (Jurnal Idea Hukum, 2023)
AbstractIn the event that there is an investigation of a criminal act of corruption carried out by law enforcement officials in the implementation of an activity sourced from the State Budget (APBN) or Regional Budget (APBD), it must first be proven by the results of supervision / examination of state financial management responsibilities carried out by an institution that has the authority to do so. Based on the theory of the source of authority and the granting of authority, the Supreme Audit Agency (BPK) is a state institution that is attributively authorized to determine state financial losses in the implementation of the APBN and APBD. However, in practice, law enforcement officials coordinate and request official assistance from the government internal supervisory apparatus (APIP) in the context of calculating state financial losses in investigating corruption crimes.Keywords: BPK, APIP, state financial losses. AbstrakDalam hal terdapat penyidikan tindak pidana korupsi yang dilakukan oleh aparat penegak hukum dalam pelaksanakan suatu kegiatan yang bersumber dari Anggaran Pendapatan dan Belanja Negara (APBN) atau Anggaran Pendapatan dan Belanja Daerah (APBD), maka harus dibuktikan terlebih dahulu dengan hasil pengawasan/pemeriksaan tangggung jawab pengelolaan keuangan negara yang dilakukan oleh lembaga yang memiliki kewenangan untuk hal tersebut. Berdasarkan teori sumber wewenang dan pemberian wewenang, Badan Pemeriksa Keuangan (BPK) merupakan lembaga negara yang secara atribusi diberikan wewenang untuk menetapkan kerugian keuangan negara dalam palaksanaan APBN dan APBD. Namun dalam prakteknya aparat penegak hukum berkoordinasi dan meminta bantuan kedinasan kepada aparat pengawasan intern pemerintah (APIP) dalam rangka penghitungan kerugian keuangan negara dalam penyidikan tindak pidana korupsi.Kata Kunci: BPK, APIP, kerugian keuangan negara.